Touristes au service de l’État: Le récit de voyage comme un instrument contre l’indifférence coloniale? - Mihályi, Dorottya (Études sur la Région Méditerranéenne, 2020)
To enlarge the territory and expand power and interest, every country uses different instruments. The propaganda, which is dedicated to convince public opinion for the national cause, is not only pervasive but multiform. Not only posters, discourses, TV and radio programs have the force to modify the conception, but ordinary people can become instrument of propaganda. The traditional role that we attribute to travellers is to vulgarise new knowledges, but we should not forget that they serve, in any case, political interests and governance. It is not rare, that a nation profits of the travellers to defend a cause, which has not surely positive reception. The manner is not complicated: the traveller has only to paint an image favourable and hide every negative points of the ruling system. He can easily become procurer of colonialism, without doing something else but underline the success of French people in the colonized territories and the results of the “civilizing mission”, which is one of the principal reasons of colonisation. The traveller can serve the propaganda of other nations too, this is the case for example in regard to the Soviet Union, which manipulates foreign travellers, thus creating theatral background to mislead them and make them write and publish their travel experiences. We can consider the traveller as an important instrument of national state building processes. Therefore, I tend to present in my paper the manipulative role of travelogues on public opinion.